1987
DOI: 10.1046/j.1468-2982.1987.0703167.x
|View full text |Cite
|
Sign up to set email alerts
|

“Hemicrania Continua”: A New Clinical Entity or a Further Development from Cluster Headache?: A Case Report

Abstract: A case of "hemicrania continua" after cluster headache in the same subject is described. Indomethacin exerted an absolute, persistent effect on the present headache. Even though our data are insufficient to demonstrate a causal relation between the two forms of headache, they do suggest this real possibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…4. A case recently observed by us which by and large is consistent with the original concept of HC (7).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…4. A case recently observed by us which by and large is consistent with the original concept of HC (7).…”
supporting
confidence: 79%
“…The lack of acetylsalicyclic acid effect in some of these cases may be real but may also be only apparent, due to the rather low dosage given (4,5). The clinical picture, on the basis of the somewhat extended experience, seems largely to be in harmony with the original description: A continuous, unilateral headache that is rather mono-symptomatic; in addition to the slight epiphora, phonophobia, and photophobia noted originally, a slight tendency to nausea (and vomiting) may be an integral part of the headache.…”
Section: General New Information From the Most Recent Casesmentioning
confidence: 99%
“…[2] Subsequently cases of HC in association with other primary headache disorders have been reported [ Table 1]. [2][3][4][5][6][7][8][9] In most of these cases, HC evolved from another primary headache disorder. There are only two case reports in whom HC and another primary headache disorder occurred concurrently, similar to our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Centonze et al [11] reported a patient who evolved from episodic cluster headache into the continuous stage of HC. Pareja et al [12] reported a patient who began in the continuous stage, but 5 years later, after discontinuing indomethacin, remained pain free.…”
Section: Remitting/continuous Coursementioning
confidence: 99%